Synthesis, Characterization, and Application of Ag-Biochar Composite for Sono-Adsorption of Phenol - Khan, Muhammad Naeem; Siddique, Maria; Mirza, Nosheen; Khan, Romana; Bilal, Muhammad; Riaz, Nadia; Waheed, Ummara; Shahzadi, Irum; Ali, Asmat; Abdellattif, Magda H.; El-Saber Batiha, Gaber; Al-Harrasi, Ahmed; et al. (Frontiers in Environmental Science, 2022)
The silver-embedded wheat straw biochar (Ag–WBC) composite was tailored effectively via the green synthetic route and was used as a nano-adsorbent for the removal of phenol by using adsorption and sono-adsorption processes. Ligustrum lucidum leaf extract was employed as a reducer to prepare silver nanoparticles, and biochar was synthesized from wheat straw via pyrolysis at 450–500°C. The synthesized biochar and Ag–WBC were characterized by using UV–Vis, SEM, EDX, and FTIR. The study confirms the ability of plant leaf extract of L. lucidum to synthesize AgNPs and Ag–WBC composites for the first time. UV–vis spectroscopic analysis confirms the formation of AgNPs and Ag–WBC composites (400–440 nm). SEM results showed that the size of the Ag–WBC composite is in the range of 80–100 nm. The elemental profile of the synthesized Ag–WBC composite shows a higher count at 3 kev due to silver. FTIR analysis revealed the presence of various functional groups involved in reducing Ag metal ions into Ag nanoparticles onto the surface of the composite. Batch experiments executed adsorption and sono-adsorption studies on WBC and Ag–WBC composites, and the results revealed that under optimum conditions, that is, pH= 3, adsorbate concentration= 10 mg L−1, adsorbents dosage= 0.05 g, time= 90 min, and US power = 80 W, the phenol removal efficiencies onto Ag–WBC composite were 78% using sono-adsorption compared to the non-sonicated adsorption. Langmuir and Freundlich isotherm models for fitting the experimental equilibrium data were studied, and the Langmuir model was chosen as an efficient model for the sono-adsorption process. The feasibility of the sono-adsorption process was also evaluated by calculating kinetics.